2022
DOI: 10.3390/medicina58101446
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Disorders of the Central Nervous System Vessels: Narrative Review

Abstract: Inflammatory disorders of the central nervous system (CNS) vessels, also called CNS vasculitides, can cause substantial disability or even be fatal. Inflammation of the CNS vessels can be caused by primary angiitis of the CNS (PACNS), inflammatory cerebral amyloid angiopathy, or systemic inflammatory disorders. Clinical symptoms of these disorders are often non-specific, such as encephalopathy, cognitive and affective abnormalities, headache and focal neurological symptoms. Diagnostic workup includes a thoroug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…Due to the fact that our patient had RVCS and Raynaud’s phenomenon, the issue arises as whether or not there is a causal connection between the two conditions. Although the surgical history of breast implants in our case was not directly linked with RCVS in SLE, studies have also reported the use of immunosuppressant drugs, especially tocilizumab, prednisolone, and cyclophosphamide, and blood transfusion as a rare yet potential cause of RCVS when used as a treatment for connective tissue diseases [ 19 , 20 , 21 , 22 ]. Studies have also revealed the presence of RCVS in pediatric patients with SLE following immunosuppressive treatment for lupus nephritis, thereby mandating its early recognition, which may help adjust further treatment [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Due to the fact that our patient had RVCS and Raynaud’s phenomenon, the issue arises as whether or not there is a causal connection between the two conditions. Although the surgical history of breast implants in our case was not directly linked with RCVS in SLE, studies have also reported the use of immunosuppressant drugs, especially tocilizumab, prednisolone, and cyclophosphamide, and blood transfusion as a rare yet potential cause of RCVS when used as a treatment for connective tissue diseases [ 19 , 20 , 21 , 22 ]. Studies have also revealed the presence of RCVS in pediatric patients with SLE following immunosuppressive treatment for lupus nephritis, thereby mandating its early recognition, which may help adjust further treatment [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 88%
“…Both conditions may develop acute severe headaches, localize neurological impairments, and cause distinctive abnormalities in brain images [ 20 ]. Moreover, vasculitis is associated with persistent inflammation with insidious-onset headache, which progresses gradually [ 21 ]. In contrast, RCVS is associated with acute ‘thunderclap headaches,’ which are self-limiting and a typical characteristic, as demonstrated in our case [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCNSV is a life-threatening condition characterized by granulomatous inflammation within small cerebral blood vessels [1,2]. The disease is rare, with an estimated annual incidence of 2.4 cases per 1,000,000 person-years, and it affects people of all ages with slight predominance in the seventh decade of life [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…PCNSV is a life-threatening condition characterized by granulomatous inflammation within small cerebral blood vessels [1,2]. The disease is rare, with an estimated annual incidence of 2.4 cases per 1,000,000 person-years, and it affects people of all ages with slight predominance in the seventh decade of life [2,3]. Diagnosis of PCNSV is challenging as it lacks standardized criteria, presents with subtle, nonspecific symptoms, and has a broad differential diagnosis, including intracranial atherosclerosis, reversible cerebral vasoconstriction syndrome, infectious and immune-mediated encephalitis, demyelinating syndromes, and neoplasms [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%